2022
DOI: 10.1259/bjr.20211125
|View full text |Cite
|
Sign up to set email alerts
|

A review of inferior vena cava filters

Abstract: The care of patients with venous thromboembolism (VTE) is delivered via a multidisciplinary team. The primary treatment for VTE is anticoagulation however, placement of filter devices in the inferior vena cava (IVC) to prevent embolization of deep venous thrombosis (DVT) is a well-established secondary treatment option. However, many controversies remain regarding utilization and management of filters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 88 publications
1
7
0
Order By: Relevance
“…Hence, IVCT may carry a greater risk of lethal PE, and placing a filter may be considered given the more extensive and possible free-floating thrombus. 22 In the present study, we found 33.0% of patients with IVCT had suffered from concomitant PE. Temporary filters were inserted into the IVC above or below the renal vein in 54.7% of patients with extensive thrombus or thrombus exceeding through the tip of the original IVCF that were evaluated as potentially life-threatening prior to further treatments.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Hence, IVCT may carry a greater risk of lethal PE, and placing a filter may be considered given the more extensive and possible free-floating thrombus. 22 In the present study, we found 33.0% of patients with IVCT had suffered from concomitant PE. Temporary filters were inserted into the IVC above or below the renal vein in 54.7% of patients with extensive thrombus or thrombus exceeding through the tip of the original IVCF that were evaluated as potentially life-threatening prior to further treatments.…”
Section: Discussionsupporting
confidence: 49%
“…Although acute IVCT is less frequently identified, its related complications are significant and alarming. 22 The GARFIELD-VTE trail demonstrated that IVCT patients had a higher risk of allcause mortality rate (13.28% vs 4.91%) compared to those patients who underwent LEDVT. 24 Alkhouli et al 17 found that patients treated with CDT had a 1.62-fold higher rate of inhospital PE than those who underwent anticoagulation, and Nagarsheth et al 14 found that patients who suffered from postprocedure PE may have benefited from a temporary filter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 Embolized thrombus can accumulate within IVC filters as designed; nonetheless, thrombogenicity can also contribute to filter thrombosis. 1 The risk of PE in cases of thrombosed IVC filters has limited treatment options and led to temporary filters often remaining unretrieved. A systematic review reported that only 34.9% of retrievable IVC filters placed for a temporary indication had been removed.…”
Section: Discussionmentioning
confidence: 99%
“…Placement of an inferior vena cava (IVC) filter is indicated when patients are at high risk for pulmonary embolism (PE) and have either cardiopulmonary comorbidities or anticoagulation contraindications. 1 The aim of IVC filter placement is to prevent embolized thrombus from reaching the pulmonary arteries. However, the benefit of filters for PE occurrence has remained unresolved.…”
mentioning
confidence: 99%